2010
DOI: 10.1103/physreva.81.022902
|View full text |Cite
|
Sign up to set email alerts
|

Stopping power of fluorides and semiconductor organic films for low-velocity protons

Abstract: A combined experimental and theoretical study of the energy loss of protons in fluorides and organic films is presented. The measurements were performed in fresh AlF 3 , LiF, and N ,N -bis(1-ethylpropyl)-perylene-3,4,9,10tetracarboxdiimide (EP-PTCDI) evaporated in situ on self-supported C or Ag foils, covering the very low energy range from 25 keV down to 0.7 keV. The transmission method is used in combination with time-of-flight (TOF) spectrometry. In the case of fluorides with large band gap energies (AlF 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…For H projectiles, " behaves similar to other insulators with comparable band gap, like LiF, AlF 3 , or KCl [21,23]. In contrast, for He projectiles, no clear threshold in the SCS was observed.…”
mentioning
confidence: 40%
See 1 more Smart Citation
“…For H projectiles, " behaves similar to other insulators with comparable band gap, like LiF, AlF 3 , or KCl [21,23]. In contrast, for He projectiles, no clear threshold in the SCS was observed.…”
mentioning
confidence: 40%
“…Very recent experiments demonstrated that below a certain velocity threshold no energy can be transferred to the electronic system of such an insulator. This occurs, however, at much lower ion velocity than expected [21][22][23]. Theoretical approaches by time-dependent density functional theory (DFT) are about to explain qualitatively the origin of the observed effect [24].…”
mentioning
confidence: 91%
“…19 Comparable phenomena are known for systems with an excitation threshold for electron-hole pair creation, e.g., noble gases or band gap materials. [20][21][22][23] For all noble metals at proton velocities ∼0.2 a.u., S is observed to become velocity proportional again. The velocity for which the transition between different regimes is observed depends on the binding energy of the d states, [24][25][26] which gives confidence in the interpretation of the velocity scaling of ε for protons due to the nontrivial density of states in noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…For large band gap insulators, electronic stopping was found to vanish below a threshold velocity vth -e.g., for LiF (band gap Eg,LiF  13.6 eV) at velocities lower than vth  0.1 a.u. [14,15]. Note that vth for LiF is considerably lower than the kink velocity for Au (vk  0.2 a.u.…”
mentioning
confidence: 99%